Theory of Transformative Learning: Adult Education in the Context of “Liquid Modernity” - Gorbunova, Lyudmila (Filosofiya osvity. Philosophy of Education, 2013)
Modernity is characterized by profound changes in all spheres of human life caused by the global transformations on macro and micro levels of social existence. These changes allow us to speak about the present as the era of civilizational transition, which is characterized by «thinning» the former «dense» hierarchical structures and institutions, and the continuous emergence of new, plastic, «fluid» rhizomatic structures in the mode of uncertainty. Individual, thrown out of safe and stable niches of his/her existence by tectonic systems shifts in the terminals of ‘space of flows’ and ‘timeless time’, is forced to head off to a nomadic journey of self-transformations for a period of individual own life. In this context, the question of what modern education should be to become really modern, arises. The dominant role in the dynamics of adult education landscape belongs to transformative learning. The transformative adult learning theory is considered as the relevant approach to education of the individual, which is able to become an autonomous communicative actor of the civil society in the situation of a «Liquid Modernity» in the given article.